1981
DOI: 10.1080/01651269.1981.10553415
|View full text |Cite
|
Sign up to set email alerts
|

On the Functions of Quinonoid Pigments in Sea Urchin Embryos

Abstract: 17Echinochrome A, an active inhibitor of lipid peroxidation, was found to appear and accumulate in developing sea urchin embryos. Complex mutual effects of various components of extracts from sea urchin embryos were noted to take place with methyl oleate peroxidation. These effects may reveal the functional role of naphthoquinones in sea urchins. sea urchin eggs; embryos; echinochrome A; antioxidative action INTRODUCTION In addition to carotenoids and melanin, which are widespread in the animal kingdom, sea ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 3 publications
0
18
0
1
Order By: Relevance
“…Previously, Koltsova et al, using thin layer chromatography (TLC), found only one pigment, echinochrome A, in extracts of non-fertilized eggs, embryos at the gastrula stage, and pluteus of sand dollar Scaphechinus mirabilis [ 59 ]. Recent mass spectrometric studies have shown that the pigment composition in the eggs and embryos of this sea urchin is more diverse.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Koltsova et al, using thin layer chromatography (TLC), found only one pigment, echinochrome A, in extracts of non-fertilized eggs, embryos at the gastrula stage, and pluteus of sand dollar Scaphechinus mirabilis [ 59 ]. Recent mass spectrometric studies have shown that the pigment composition in the eggs and embryos of this sea urchin is more diverse.…”
Section: Resultsmentioning
confidence: 99%
“…Using dissociated sea urchin embryos transfected with the yeast gene gal4, we have previously shown that the absorption spectrum of red-brown pigments extracted from the cultured cells coincides with that of echinochrome [ 28 ]. The number of cells containing the red-brown pigments in two-month-old cell culture reached 50–60%, while the number of naphthoquinone pigments in these cells, as calculated per one cell [ 29 ], increased 9-10-fold [ 28 ] compared to the cells of normal plutei in vivo [ 5 ]. Here, we continued the studies of the differentiation process of sea urchin pigment cells in culture and developed conditions for the promotion of pigment cell differentiation without transfection of sea urchin embryos with foreign genes.…”
Section: Discussionmentioning
confidence: 99%
“…Like many marine secondary metabolites, polyketide compounds are known for their highly effective antioxidant, antibacterial, antifungal, and antitumor activities. In addition, these compounds may play decisive roles in the regulation of lipid peroxidation and in immune defense [ 3 , 4 , 5 , 6 ]. They are generated via a series of enzymatic, oxidative and photochemical reactions from shikimic acid (ShA)—a precursor of naphthoquinone pigments ( Figure 1 ) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%